Emission of volatile organic compounds from new furniture products and its impact on human health. Issue 7 (3rd October 2019) - Yan, Meihong; Zhai, Yunbo; Shi, Pengtu; Hu, Yanjun; Yang, Haijian; Zhao, Hongjie
ABSTRACT: The emissions of volatile organic compounds (VOCs) from two new furniture including footstool and bedside table, were measured in an environmental chamber. Nine VOCs including benzene, toluene, ethylbenzene, m/p-xylene, o-xylene, styrene, n-undecane, and n-butyl acetate were identified and quantified by thermal desorption and gas chromatography. The effect of loading rate (the ratio of the furniture surface area to the chamber volume) on VOCs emissions was investigated. The release of dominant organics differed with the furniture and significant differences were observed at different loading rates. The change of VOCs concentrations showed a good fit with results from a double-exponential decay model. When the loading rate was doubled, the VOCs concentrations of footstool and bedside table increased 1.108–2.096 and 1.116–3.095 times, respectively. Moreover, human health impact due to pollutants released from new furniture at various loading rates was assessed. By simulating VOCs emissions from bedside table in the indoor conditions previously, the maximum value of HI (non-cancer risk hazard index) at high loading rate (3.6 m 2 /m 3 ) for six pollutants (toluene, ethylbenzene, m/p-xylene, o-xylene and styrene) was 12.8 times higher than the public acceptable value, implying high non-cancer risk. The present work should be valuable for evaluating VOCs emissions and the relevant human health effects from new furniture.